2021
DOI: 10.1029/2020gh000380
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiology of Metal Mine Waste: Bioremediation Applications and Implications for Planetary Health

Abstract: Microbes colonise and inhabit mine wastes, they tolerate high concentrations of metals and contribute to soil functioning and plant growth  Microbes transform metal speciation and environmental mobility, through metabolism, biogeochemical cycling and metal resistance mechanisms  Beneficial microbial activity can be stimulated to remediate metal-containing mine wastes, but more long-term field studies are required

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 474 publications
0
12
0
Order By: Relevance
“…P. pseudoalcaligenes CECT 5344 was grown with different concentrations of arsenite (up to 1 mM), using either ammonium or cyanide as the sole nitrogen source ( Figure 1 B). It was observed that, with both nitrogen sources, a concentration of 0.25 mM of arsenite, almost 10 times higher than the average concentration of arsenic in the lithosphere [ 51 ], conditioned cell growth sufficiently without being highly detrimental to bacterial growth ( Figure 1 B). Likewise, P. pseudoalcaligenes CECT 5344 was highly resistant to As(V), but it was observed that 200 mM arsenate negatively affected bacterial growth ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…P. pseudoalcaligenes CECT 5344 was grown with different concentrations of arsenite (up to 1 mM), using either ammonium or cyanide as the sole nitrogen source ( Figure 1 B). It was observed that, with both nitrogen sources, a concentration of 0.25 mM of arsenite, almost 10 times higher than the average concentration of arsenic in the lithosphere [ 51 ], conditioned cell growth sufficiently without being highly detrimental to bacterial growth ( Figure 1 B). Likewise, P. pseudoalcaligenes CECT 5344 was highly resistant to As(V), but it was observed that 200 mM arsenate negatively affected bacterial growth ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, once oxidised, potentially toxic elements previously adsorbed onto the surface or associated with pyrite are released to the solution [7,8]. Although many acidophiles can obtain carbon autotrophically, their growth and metabolic activity in mine waste may be limited by the availability of other essential nutrients, such as nitrogen and phosphorus [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Colony growth of SRB can be inhibited by extreme conditions such as high pressure, radiation, and heat. However, because SRB is a spore-forming bacteria that can endure harsh conditions, the growth activity cannot be eliminated [32,33].…”
Section: Discussionmentioning
confidence: 99%